2015
DOI: 10.1146/annurev-bioeng-071813-104938
|View full text |Cite
|
Sign up to set email alerts
|

Viral Vectors for Gene Therapy: Translational and Clinical Outlook

Abstract: In a range of human trials, viral vectors have emerged as safe and effective delivery vehicles for clinical gene therapy, particularly for monogenic recessive disorders, but there has also been early work on some idiopathic diseases. These successes have been enabled by research and development efforts focusing on vectors that combine low genotoxicity and immunogenicity with highly efficient delivery, including vehicles based on adeno-associated virus and lentivirus, which are increasingly enabling clinical su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
288
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(298 citation statements)
references
References 147 publications
(219 reference statements)
4
288
0
6
Order By: Relevance
“…In scale-up to larger animals and humans, FUS also benefits from the use of phased array sources and imagebased aberration correction 9, 58-61 . Additional work is needed to make AAV vectors more efficient to reduce their required dose, and to make compact cell-type specific promoters that work robustly in primates 24 . Finally, ongoing studies of the pharmacokinetics of CNO and clozapine 62 will enable the optimization of ligand dosing for DREADD activation or motivate the use of available alternative ligands 63 or chemogenetic receptors 64,65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In scale-up to larger animals and humans, FUS also benefits from the use of phased array sources and imagebased aberration correction 9, 58-61 . Additional work is needed to make AAV vectors more efficient to reduce their required dose, and to make compact cell-type specific promoters that work robustly in primates 24 . Finally, ongoing studies of the pharmacokinetics of CNO and clozapine 62 will enable the optimization of ligand dosing for DREADD activation or motivate the use of available alternative ligands 63 or chemogenetic receptors 64,65 .…”
Section: Discussionmentioning
confidence: 99%
“…ATAC combines FUS with replication-incompetent AAV vectors, an established method to stably transfect mammalian cells without integration into the target genome. AAV is widely used in neuroscience research, and has recently shown promise in the clinic [20][21][22][23][24] . When a gene of interest carried by AAV is encoded under an appropriate promoter, the expression of this gene can be restricted to a specific class of neurons 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The scope for therapeutic strategies has broadened and now encompasses vectors for replacement protein expression, gene therapy and the treatment of cancer [2,3]. Viruses for in vivo applications show a limited affinity for their target cells, they are generally unstable and large doses of infective virus particles (up to 10 12 active virus particles per dose) are needed to achieve a therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Although much progress on clinical application has been made within viral vectors such as adeno-associated virus (AAVs), and retrovirus, plasmid-based non-viral complex systems are always in great demand in pre-clinical research. [3][4][5][6] Apoptosis is a physiological cell suicide program that is critical for the maintenance of healthy tissues. 7 Inducing apoptosis in tumor cells by delivering suicide gene encoded plasmids has been proved to be efficient for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%